SISTEM PENANGGULANGAN TINDAKAN KEKERASAN OLEH WALI SISWA TERHADAP PENDIDIK SMK NEGERI 2 MAKASSAR - Aan Aswari; Salim Basamalah; Amar Bachti; Muhammad Rinaldy Bima (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2017)
The high school / vocational school situation is following the modern school model in order to adapt its existence to technology era. Synchronization can make more excellence, including in the form of cross-border regional relationships and forming a competitive atmosphere between schools, and build new subsystems to improving the quality of schools, but in fact also poses an additional challenge in running the subsystems within the school, thus requiring a legal approach as a solution to potential conflicts. The method of implementation in this devotion uses a lecture socialization technique in order to create a legal awareness for students, teachers and parents in order to prevent legal problems. Socialization and application of legal symbols for transfer of knowledge to school elements isn’t biased after the dedication to the students has been completed. This dedication emphasizes four important points, including: (1) Religious Approach, (2) Student Moral & Ethics Development, (3) The Importance of Discipline, and (4) Embedding Legal Awareness, which is believed to help keep the school process to its goals any time. Finally, all these important points become the reference for the implementation of concrete activities in the environment of SMK Negeri 2 Makassar.Keywords: violence, vocational students, student trusteeABSTRAKSituasi sekolah setingkat SMU/Kejuruan telah mengikuti perkembangan model sekolah moderen dalam rangka menyesuaikan eksistensinya diera teknologi. Sinkronisasi diyakini dapat meningkatkan keunggulan, diantaranya dalam bentuk pergaulan lintas batas kewilayahan dan membentuk suasana kompetitif antar sekolah. Hal itu menumbuhkan berbagai subsistem baru dalam peningkatan mutu sekolah, namun sesungguhnya menimbulkan sebuah tambahan tantangan dalam menjalankan subsistem dalam sekolah tersebut, sehingga perlu pendekatan hukum sebagai solusi terhadap potensi konflik. Metode pelaksanaan dalam pengabdian ini menggunakan tehnik ceramah/sosialisasi agar terciptanya sebuah kesadaran hukum bagi siswa, guru dan wali siswa demi mencegah permasalahan hukum. Sosialisasi dan penerapan simbol hukum agar transfer ilmu pengetahuan kepada unsur dalam sekolah tidak bias setelah pengabdian pada siswa telah selesai. Pengabdian ini menekankan pada 4 poin penting, diantaranya: (1) Pendekatan Keagamaan, (2) Pengembangan Moral & Etika siswa, (3) Pentingnya Kedisiplinan, dan (4) Menanamkan Kesadaran Hukum, yang diyakini mampu membantu menjaga proses sekolah meraih tujuan-tujuannya setiap saat. Akhirnya, keseluruh poin penting ini menjadi acuan untuk dilaksanakannya berbagai kegiatan kongkrit dalam lingkugan sekolah SMK Negeri 2 Makassar.Kata kunci: kekerasan, siswa SMK, wali siswa